Exposure to mercury among 9-year-old Spanish children: Associated factors and trend throughout childhood - Raquel Soler-Blasco; Mario Murcia; Manuel Lozano; Xabier Aguinagalde; Gorka Iriarte; Maria-Jose Lopez-Espinosa; Jesús Vioque; Carmen Iñiguez; Ferran Ballester; Sabrina Llop (Environment International, 2019)
Mercury is considered a neurotoxicant and human exposure occurs mainly from the consumption of marine species. We aimed to describe total mercury concentrations (THg) and associated factors in 9-year old children, as well as to explore the trend in THg from 4 to 9 years of age. The study population consisted of 9-year-old children participating in the INMA (Environment and Childhood) birth cohort study in Valencia, Spain (n = 405, 2013–2014). THg in hair samples was measured by atomic absorption spectrometry at the age of 4 and 9 years. Sociodemographic and dietary data was obtained through questionnaires. Multiple linear regression was used to explore the association between THg and covariates.The geometric mean (95% confidence interval) of hair THg at 9 years old was 0.89 μg/g (0.81, 0.98). Thirteen percent of children had THg above the equivalent to the Provisional Tolerable Weekly Intake proposed by the World Health Organization. THg were higher among children whose mothers had a healthy body mass index before pregnancy. Children with non-smoker mothers and worker fathers had also higher THg. Children's fish intake at 9 years-old was positively associated with THg, being swordfish, canned tuna and lean fish (i.e. hake, sea bream and sole) the most associated categories. Levels decreased by around 22% between 4 and 9 years old.Birth cohort studies, such as the INMA Project, allow the longitudinal evaluation of Hg exposure and the possible effects on children's health. This information can be used to formulate diet recommendations in vulnerable populations. Keywords: Mercury, Child, Diet exposure, Environmental exposure, Postnatal exposure, Spain